IMPLEMENTASI METODE JIBRIL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN AL-QUR'ANMATERI SURAH AL-HUJURAT/49:13 KELAS IV SDNEGERI 2 JEDONG - Bayidi, Ahmad; Gafur, Abd.; Barizi, Ahmad (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the problem. What are the results of learning the Al-Qur'an using the Jibril method and audio-visual media on the material Surah Al-Hujurat/49:13 Class IV SD Negeri 2 Jedong Wagir Academic Year 2023/2024? Meanwhile, the aim of this research is to improve students' ability to read the Al-Qur'an and the quality of Al-Qur'an learning in the Islamic Religious Education learning process on the material